Palladium Catalyzed Annulation of o‑Iodo-Anilines with Propargyl Alcohols: Synthesis of Substituted Quinolines - Zhang, Zhi; Deng, Jing-Tong; Feng, Jia-Yi; Liang, Jin-Yan; Xu, Xue-Tao; Peng, Jin-Bao (Journal of organic chemistry, 2023)
A palladium catalyzed annulation of o-iodo-anilines with propargyl alcohols for the synthesis of substituted quinolines has been developed. The reaction tolerates diverse functional groups under mild conditions, providing direct access to 2,4-disubstituted quinolines from easily available starting materials. A broad range of 2,4-disubstituted quinolines were efficiently prepared in good to excellent yields.